Abatacept for the treatment of adults with psoriatic arthritis: patient selection and perspectives - Noisette A; Hochberg MC (Dove Medical Press, 2018)
Ashley Noisette, Marc C Hochberg Division of Rheumatology and Clinical Immunology, Department of Medicine, University of Maryland School of Medicine, Baltimore, MD, USA Abstract: Psoriatic arthritis (PsA) is a heterogeneous disease with several clinical subtypes including peripheral arthritis, dactylitis, enthesitis, nail disease, and axial arthritis. Nonsteroidal anti-inflammatory drugs, glucocorticoids, and conventional disease-modifying agents are used as first line in the treatment of active PsA. For moderate-to-severe PsA failing conventional therapy, antitumor necrosis factor inhibitors have historically been the drugs of choice. In recent years, novel interleukin-23/interleukin-17 pathway targets such as ustekinumab and secukinumab, and phosphodiesterase-4 inhibitor apremilast have been approved for use in the United States and Europe. Two sets of recommendations for the management of PsA were published in 2016 with consideration for these newer therapies. Since then, the results from a Phase III randomized controlled trial demonstrated that abatacept has efficacy in the treatment of PsA. Abatacept, a cytotoxic-T-lymphocyte-associated antigen 4 (CTLA-4)–Ig human fusion protein, acts to prevent naïve T-cell activation through the inhibition of the critical CD28 co-stimulatory signal. In the 2017 Active Psoriatic Arthritis Randomized Trial (ASTRAEA), 424 participants were randomized 1:1 to receive subcutaneous abatacept 125 mg weekly versus placebo. At week 24, 39.4% of those who received abatacept achieved a minimum of 20% improvement in the American College of Rheumatology (ACR) response compared to 22.3% in the placebo arm, a statistically significant finding (P<0.001). The 2011 Phase II study published by Mease et al demonstrated statistically significant improvements in the ACR20 response by week 169 in participants treated with intravenous abatacept 10 mg/kg (48%) and 30/10 mg/kg (42%) when compared with placebo (19%). This article reviews the data supporting the efficacy of abatacept in the management of PsA and attempts to place this agent in the context of other biologic disease-modifying antirheumatic drugs and targeted small molecules used in the treatment of patients with PsA. Keywords: biologic DMARD, psoriasis, T-cell inhibition, targeted small molecules